The relationship between congenital heart defects and e-nos gene in down syndrome - Okur, Mesut; Eröz, Recep; Bektaş, Mehmet Selçuk; Gülşen, Süleyman; Bahadır, Anzel; Türker, Yasin; Güneş, Cemalettin (Medecine Et Hygiene, 2016)
The relationship between congenital heart defects and e-NOS gene in Down syndrome: The aim of the study was to compare the effects of three eNOS gene polymorphisms associated with congenital heart defects, between Down syndrome patients with and without cardiac anomalies. Transthoracic echocardiographic examinations and eNOS single-nucleotide polymorphis ms were investigated on seventy-five patients, prospectively. The frequencies of mutant alleles in the eNOS promoter (the -786T/C polymorphism) and exon 7 mutant alleles (the 894G -> T polymorphism) were significantly higher in Down syndrome patients with and without cardiac anomalies. The frequency of the intron G10T polymorphism did not significantly differ between patients with and without cardiac anomalies. We found a significant relationship between eNOS gene polymorphisms and the congenital heart defects in patients with Down syndrome. Screening for the presence or absence of eNOS polymorphisms may be useful to obtain preliminary data on the risk of congenital heart defects in patients with Down syndrome.
WOS: 000395220700001
PubMed ID: 30204958
Keywords: Enos; Down Syndrome; Trisomy 21; Congenital Heart Defects